2016
DOI: 10.4143/crt.2015.061
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Weekly Paclitaxel Plus Gemcitabine as a Second-Line Therapy in Patients with Metastatic or Recurrent Small Cell Lung Cancer

Abstract: PurposePaclitaxel (P) and gemcitabine (G) are clinically synergistic in small cell lung cancer (SCLC). We evaluated the efficacy of PG as a salvage treatment for SCLC patients whose disease progressed after a platinum-containing regimen.Materials and MethodsEligibility included histologically confirmed SCLC, one dimensionally measurable disease, Eastern Cooperative Oncology Group performance status 0-2, and progressive disease after platinum-based chemotherapy. Treatment consisted of P (80 mg/m2) and G (1,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…For more than a decade, no new substances were approved to treat relapsed or refractory (R/R) advanced or metastatic disease despite a multitude of prospective clinical trials, including cytotoxic agents, 4 10 antibodies, 11 , 12 and targeted therapies. 13 17 …”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, no new substances were approved to treat relapsed or refractory (R/R) advanced or metastatic disease despite a multitude of prospective clinical trials, including cytotoxic agents, 4 10 antibodies, 11 , 12 and targeted therapies. 13 17 …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the toxicities were tolerable . Gemcitabine was also selected for recurrent lung cancer patients . Gemcitabine may be relatively safe in heavily pretreated patients with cancers other than ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PTX is one of the most frequently prescribed medications in Japanese clinical practice to treat recurrent SCLC and the efficacy of nanoparticle albumin-bound (nab)-PTX monotherapy might be moderate for heavily treated, relapsed SCLC patients (19). Several studies reported the use of PTX combined with carboplatin, gemcitabine or albumin-bound PTX nanoparticles for the treatment of metastatic or recurrent SCLC, indicating that PTX as second-line chemotherapy is a good choice for the treatment of patients with SCLC (48)(49)(50). After nano-microsized modification, PTX is an ideal drug for the treatment of SCLC due to its improved therapeutic efficiency and diminished side effects.…”
Section: Iron Oxide Nanoparticles Induce Ferroptosis Via the Autophag...mentioning
confidence: 99%